Implementation Of The Think Pair Share Model Assisted By Canva Video On The Topic Of Salt Hydrolysis For The Learning Outcomes Of 11th Grade Science Students - Talitha Az Zahra Rosadi; Parham Saadi; Muhammad Kusasi (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2024)
Research has carried to implement the Think Pair Share (TPS) model with the help of Canva videos in teaching about salt hydrolysis for 11th-grade students at SMAN 10 Banjarmasin. This study aims to compare the learning outcomes between the implementation of the Think Pair Share model with Canva video assistance and  the Discovery Learning model on the focus of salt hydrolysis. This research employed a quantitative method with a quasi-experimental design using the pretest-posttest nonequivalent control group design. The research participants formed students from SMAN 10 Banjarmasin, with XI MIPA 2 class as the experimental group and XI MIPA 3 class as the control group. The teaching model considered the independent variable, while the learning outcomes were the dependent variable. Data collected through tests and non-tests also were analyzed using descriptive and inferential analysis techniques. The research results showed that there occured to be a difference in learning outcomes in the knowledge domain between the students in the experimental group with an achievement percentage of 96.77% and the students in the control group with an achievement percentage of 80.65%. There was also a difference in learning outcomes in the skills domain, with the experimental group obtaining a score of 3.42 and the control group acquiring a score of 3.21. Meanwhile, the learning outcomes in the attitude domain showed a score of 3.42 for the experimental group and an score of 3.44 for the control group. Thus, it can resolved that there is a difference in the learning outcomes of students who use the Think Pair Share model with Canva video assistance compared to the Discovery Learning model on the focus of salt hydrolysis.